Criminal or nay?” Migrants’ administrative detention within the IAHRS: - Lorenzo Bernardini (Revista Brasileira de Direito Processual Penal)
In this paper, several aspects of the administrative detention discipline in the light of the Inter-American Human Rights System (IAHRS) standards will be addressed. Through a comparative approach, the paper aims at assessing whether the latter provides better protection to detained migrants in respect of other regional systems, such as EU law or ECHR legal framework, from both a substantive and a procedural standpoint. In the first paragraph, a general introduction upon the structure and the aim of the IAHRS will be developed, emphasising the relevant sources of law which have been involved in the creation of such a legal framework. Then, a brief analysis specifically devoted to the migrants’ status within the IAHRS will be offered, also considering the international legal standards on the matter. In the third paragraph I will explain different aspects of administrative detention of migrants—both substantive and procedural ones—in the light of the relevant IAC(t)HR case-law, which might seem to acknowledge its de facto criminal nature. A constant reference to the analogous CJEU and ECtHR jurisprudence on the matter will be provided. Finally, a comparison between Europe and America systems upon different standards of migrants’ administrative deprivation of liberty will be presented, arguing that the IAHRS approach seems more consistent with international law and, with respect to the European legal framework, more attentive to the paramount importance of the fundamental rights and freedoms to be accorded to aliens subjected to allegedly non-criminal custodial measures.